P297 Disseminated histoplasmosis from skin to adrenals a cosmetic catastrophe—a rare case report. (20th September 2022) - R, NEETHA T; Khatod, Yash; Samantaray, Subhashree; Khichar, Satyendra; Bohra, Gopal Krishna; Kumar, Deepak; Garg, Mahendra Kumar
Abstract: Poster session 2, September 22, 2022, 12:30 PM - 1:30 PM: Background: The varying presentations of histoplasmosis is always a diagnostic dilemma for clinicians. Cases of disseminated histoplasmosis can present in multiple specialties like dermatology, medicine, endocrinology, with skin, and mucosal hyperpigmentation as the only major symptom. Case Report: Here we present a case of a 54-year-old male with hyperpigmentation all over the body with multiple specialty consultations done in the past 2 years. There was a significant history of loss of weight over a period of 2 years. His cortisol levels were low which explained the focus in the adrenals, with bilateral adrenomegaly found in imaging studies. His diagnostic work-up for TB and possible malignancy was ruled out. The provisional diagnosis of histoplasmosis was made and confirmed with biopsy and culture. Definitive treatment with antifungals was initiated, which showed improvement on follow-up. Conclusion: Histoplasmosis is always underreported, because of a lack of information regarding the various clinical presentations. Early diagnosis and prompt treatment may save the patient from catastrophic adrenal insufficiency. The diagnosis of adrenal histoplasmosis should be considered in patients presenting with constitutional symptoms and adrenal masses with or without adrenal insufficiency. Adrenal histoplasmosis can be the only possible presentation in disseminated histoplasmosis.